(untitled) (Texas Journal of Medical Science, 2025)
Breast cancer represents one of the most significant oncological challenges of the modern era and remains the most frequently diagnosed malignancy among women worldwide. According to global cancer statistics, breast cancer accounts for nearly one quarter of all female cancer cases and constitutes a leading cause of cancer-related mortality despite substantial progress in diagnosis and treatment. The increasing incidence of breast cancer is attributed to a combination of demographic aging, lifestyle changes, reproductive factors, and improved detection through screening programs. At the same time, advances in early detection have resulted in a growing proportion of patients being diagnosed at early stages of the disease, when curative treatment is achievable and long-term survival rates are high